2015
DOI: 10.5194/amt-8-1233-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MOZAIC Capacitive Hygrometer during the airborne field study CIRRUS-III

Abstract: Abstract. The MOZAIC Capacitive Hygrometer (MCH) is usually operated aboard passenger aircraft in the framework of MOZAIC (Measurement of Ozone by Airbus In-Service Aircraft) for measuring atmospheric relative humidity (RH). In order to evaluate the performance of the MCH, the instrument was operated aboard a Learjet 35A research aircraft as part of the CIRRUS-III field study together with a closed-cell Lyman-α fluorescence hygrometer (Fast in situ Stratospheric Hygrometer, or FISH) and an open-path tunable di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
0
29
0
Order By: Relevance
“…As a main conclusion, Neis et al (2015) reported a good agreement of the MCH with the reference time series (see Section 3.2), with an uncertainty of 5% RH with respect to liquid water (RH liquid ). During sequences with decreasing sensor temperature, the MCH showed a decreasing sensitivity as a consequence of the increasing response time (see Section 4.1), that is, small-scale fluctuations across strong RH gradients could not be resolved.…”
Section: Field Campaigns Cirrus-iii and Airtoss-icementioning
confidence: 65%
See 3 more Smart Citations
“…As a main conclusion, Neis et al (2015) reported a good agreement of the MCH with the reference time series (see Section 3.2), with an uncertainty of 5% RH with respect to liquid water (RH liquid ). During sequences with decreasing sensor temperature, the MCH showed a decreasing sensitivity as a consequence of the increasing response time (see Section 4.1), that is, small-scale fluctuations across strong RH gradients could not be resolved.…”
Section: Field Campaigns Cirrus-iii and Airtoss-icementioning
confidence: 65%
“…Another reason for classifying the field study data by the sensor temperature is the fact that Neis et al (2015) have observed an improvement in the agreement with the reference humidity data with increasing sensor temperature, that is, with decreasing response time of the hygrometer.…”
Section: Data Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy is ±0.5 • C for the temperature measurement and ±5 % for the detection of the relative humidity. Evaluation and measurement methods of the MCH are described in detail in Neis et al (2015).…”
Section: Trace Gas Instrumentsmentioning
confidence: 99%